Formale und informelle Politik aus institutioneller Perspektive: Ein Analyseansatz für die vergleichenden Area Studies; Formal and informal politics from an institutional perspective: An analytical approach for comparative area studies - Patrick Köllner (German Institute of Global and Area Studies (GIGA), 2005)
In diesem Papier wird das sozialwissenschaftliche Analysefeld formaler und informeller Politik ausgeleuchtet und mit einer institutionellen Perspektive verknüpft. Dazu wird zunächst die bisherige Auseinandersetzung mit diesen beiden Formen der Politik im Rahmen der vergleichenden Politikwissenschaft und der Area Studies skizziert. Daran anknüpfend wird ein eigener konzeptioneller Zugang zum Thema präsentiert. Formale und informelle Elemente der Politik werden im Weiteren aus einem institutionellem Blickwinkel betrachtet. In diesem Kontext wird auch das Verhältnis formaler und informeller Institutionen im politischen Bereich diskutiert, wobei mögliche Vor- und Nachteile, Konsequenzen und Wirkungen beider Arten von Institutionen thematisiert werden. Perspektiven der weiteren Forschung beschließen das Papier. – – Formal and informal politics from an institutional perspective: An analytical approach for comparative area studies Formal and informal politics as an object of social science analysis are connected in this paper with an institutional perspective. First, we survey the existing comparatively oriented political science and area studies literature on both forms of politics. Second, we present our own conceptual approach in this regard. In the remainder of the paper, formal and informal politics are viewed through an institutional prism. In this context we discuss the relationship between formal and informal institutions in politics, looking at advantages and disadvantages, consequences, and effects of both types of institutions. Research perspectives are highlighted in the concluding section of the paper.
Keywords: 300; Comparative Politics; Area Studies; Institutionalism; Formal Institutions; Informal Institutions